Effect of Fermentation and/or Cooking on Some Nutritional Quality of Sorghum Meals Formulated with Different Ratios of Wheat and Pumpkin Flour - Mustafa, Mayada A.; Abdallh, Almujtaba H. M.; Babiker, Elfadil E. (Food Science and Engineering, 2024)
Sorghum cultivar (Tabat), defatted pumpkin seed pulp (DPSP), and wheat flour were used to prepare four meals to study the effects of component ratio and fermentation and/or cooking on various nutritional qualities. Before and after processing, the meals' chemical compositions, total calories, minerals, antinutrients, and in vitro protein digestibility (IVPD) were assessed. The addition of wheat and pumpkin flour resulted in a decrease in carbohydrates and antinutrients and an increase in ash, protein, fiber, fat, total and extractable minerals, and IVPD. After fermentation, the antinutrients were significantly (P ≤ 0.05) reduced, resulting in meals of excellent quality. Cooking the fermented dough afterward, nevertheless, revealed much greater improvement. The proportion of ingredients decreased the effect of cooking on chemical composition and led to a substantial (P ≤ 0.05) reduction in tannin and phytate, which was accompanied by a significant (P ≤ 0.05) increase in IVPD and mineral extractability. Meals were accepted more often than the control group (P ≤ 0.05). Out of all the formulations, the one with 10% wheat and 20% DPSP flours (M3) was found to be the most nutrient-dense and bioavailable.